Karakterisasi Morfologi 51 Varietas Unggul Baru Padi (Oryza sativa L.) di Kabupaten Subang - Simamora, Praneva Annisa; Sugiono, Darso; Widyodaru S, Nurcahyo; Susanto, Untung (JURNAL AGROPLASMA, 2023)
Rice (Oryza sativa L.) is a very important commodity. The nutritional content in rice makes rice a very important commodity to meet food needs. One of the efforts that can be made to increase rice productivity is to create new superior rice varieties that have high yields. This study aims to examine and determine the varied morphological characteristics of the new superior varieties of rice, and determine how close the kinship relationship is between 51 new superior varieties of rice (Oryza sativa L.) and determine the advantages of each variety. This research was conducted at the Experimental Garden of the Indonesian Rice Research Center located in Sukamandijaya Village, Ciasem District, Subang Regency, West Java. The time for conducting the research was carried out in September 2021-March 2022. The research method used was a descriptive method, with 51 treatments of new superior rice varieties. Each treatment was repeated 3 times so that there were 153 experimental units. Each observational data on morphological characters of 51 superior rice varieties (Oryza sativa L.) was analyzed by clustering using the UPGMA method with NTSYS 2.02i and 2.11a software. The results showed that the results of the cluster analysis formed 6 main groups at a similarity coefficient value of 0.72 (72%). There are 7 closest kinship relationships and have the farthest kinship in inpari 1 and Inpago 9 varieties.Â Keywords : Characterization, Morphology, New superior varieties, Clustering, Rice